Spatiotemporal Variation in Water Quality in the Yellow River Basin - ZHANG Yan; LIANG Zhijie; ZOU Lei; LI Ping; DOU Ming; HUANG Zhongdong; QI Xuebin; GAO Qing (Guan'gai paishui xuebao, 2021)
【Background and objective】 The Yellow River is the second largest river in China, flowing through six provinces across the county from the west to the east. The rapid economic development and the increased anthropogenic activity over the past four decades, however, have resulted in changes in its runoffs and water quality both temporally and spatially. Understanding these changes can help improve water management and maintain ecological sustainability of the river. The purpose of this paper is to present the results of a survey on the water quality of Yellow River and its tributaries. 【Method】 We selected 12 sections in the river and its tributaries, and measured pH, dissolved oxygen (DO), permanganate index (CODMn) and ammonia nitrogen (NH3) in each section at different seasons. Spatiotemporal variations in these chemical properties were analyzed using the multivariate statistical method, and the quality of the water at each section was quantified using a water pollution index (WPI). 【Result】 Water quality of the river was the best in the mainstream, followed by its tributaries Huangshui River and Weihe River, with the water quality in Fen river being the worst. All four chemical properties varied spatiotemporally. The WPI measured at different seasons in the sections at Minhe Bridge in Haidong, Tongguan Suspension Bridge in Weinan, and Yuncheng Hejin Bridge in Yuncheng, reached Class IV water quality standard or above at frequencies of 66.30%, 98.91% and 78.62%, respectively. In general, the water quality of all sections was poor in spring and winter but improved in summer and autumn. During the measuring period, the WPI in all sections had been in decrease, especially the sections at Minhe Bridge in Haidong, Zhongwei Xintun, and Tianshui Niubei. Cluster analysis based on the WPI index was consistent with the spatiotemporal distribution of the pollutant concentrations, and the seasonal fluctuation in WPI at Minhe Bridge in Haidong, Tongguan Suspension Bridge in Weinan, and Hejin Bridge in Yuncheng, was higher, especially from January to March, than that in other sections. 【Conclusion】 The water quality of Yellow River and its tributaries varied spatiotemporally, but overall it has been improving.